Targeting neuroendocrine prostate cancer: molecular and clinical perspectives - Panagiotis J Vlachostergios; Christos N Papandreou (Frontiers in Oncology, 2015)
Neuroendocrine prostate carcinoma, either co-present with the local adenocarcinoma disease or as a result of transdifferentiation later in time, was described as one major process of emerging resistance to androgen deprivation therapies, and at the clinical level it is consistent with the development of rapidly progressive visceral disease, often in the absence of elevated serum prostate-specific antigen level. Until present, platinum-based chemotherapy has been the only treatment modality, able to produce a fair amount of responses but of short duration. Recently, several efforts for molecular characterization of this lethal phenotype have resulted in identification of novel signaling factors involved in microenvironement interactions, mitosis, and neural reprogramming as potential therapeutic targets. Ongoing clinical testing of specific inhibitors of these targets, for example Aurora kinase A inhibitors, in carefully selected patients and exploitation of expression changes of the target before and after manipulation is anticipated to increase the existing data and facilitate therapeutic decision making at this late stage of the disease when hormonal manipulations, even with the newest androgen-directed therapies are no longer feasible.